6(a+4)=6(a-2)

Simple and best practice solution for 6(a+4)=6(a-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(a+4)=6(a-2) equation:


Simplifying
6(a + 4) = 6(a + -2)

Reorder the terms:
6(4 + a) = 6(a + -2)
(4 * 6 + a * 6) = 6(a + -2)
(24 + 6a) = 6(a + -2)

Reorder the terms:
24 + 6a = 6(-2 + a)
24 + 6a = (-2 * 6 + a * 6)
24 + 6a = (-12 + 6a)

Add '-6a' to each side of the equation.
24 + 6a + -6a = -12 + 6a + -6a

Combine like terms: 6a + -6a = 0
24 + 0 = -12 + 6a + -6a
24 = -12 + 6a + -6a

Combine like terms: 6a + -6a = 0
24 = -12 + 0
24 = -12

Solving
24 = -12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9x8=yx8 | | 64x^2-225y^2=0 | | x^4-2x^3-14x^2-2x-15=0 | | 3y-15=12 | | 18c+16=17c | | 24a^2-15a+32a-20= | | x-2.8-0.8x=1.2 | | 3.5-12s=-5 | | 17xn=10 | | -3(-6x-7)=4x | | 2x^2-7-13=0 | |  3.4x-3x | | -6+2x=5x-6 | | 0.1+11.26=0.2h+12.5 | | 5(x-3)=8x+15 | | 5xn=600 | | 9m-28=2n | | 5a+8-4a=8 | | .1z+.3z=-8 | | (52-9)+n=62 | | 6.48=ln(x) | | 5(3b-3)= | | -7k-16-7k=124 | | -13.1y+4.38=-18.7y+9.9y-2.93 | | w+5+8w+6=29 | | 4n-7+4n=8+8n-5 | | 5x-7y+x+2x-y=0 | | =5(3b-3) | | 5(a+36)=59+156 | | 6(a+4)=6(4-2) | | 139-u=217 | | -19+17u=18u+1 |

Equations solver categories